Gamification as a strategy to enhance mathematical competence in geometry and measurement - Zavala Ortiz, Ana Gabriela; Sisalema Nastar, Dilan Mateo; Arciniegas Romero, María Gabriela; Guiz Aza, Selina Dejaneyra; Pilataxi Yacelga, Adrián Alexander (SATHIRI, 2025)
Geometry and measurement are fundamental areas of focus within the mathematics curriculum in Ecuador that promotes the development of essential cognitive skills in students. The objective of this study was to determine the incidence of the methodological strategy of gamification in the development of the mathematical competence geometry and measurement. The research was quantitative with a descriptive relational scope and quasi-experimental design, involving 144 high school students from 6 public schools in the city of Ibarra. An initial pretest analysis showed that 55% of the students had a low level of geometric competencies, while the remaining 45% had a medium or high level. These data were contrasted with those obtained in a post-test, revealing a decrease in the number of students with low level to 44%, compared to the increase of students with medium and high level to 56%. Although the initial results revealed that students were developing the assessed competency, more than half of them did not reach the expected level, indicating the need for innovative strategies to improve learning. The findings demonstrate the potential of gamification to transform geometry and measurement instruction in Ecuador. If properly adapted to the school context, this strategy could be a key tool in overcoming challenges students face in developing these skills
Keywords: Gamification; Geometry; Mathematics education